Method for determining the optimal length of the transition part of a railway track plan (Международный научный журнал «Инженер», 2026)
On a curved section of a railway track, to smooth out the turn, a curve is considered whose curvature canbe equal to the curvature of a circle, and a smooth transition is formed in an optimal way.